Effects of a Yeast Product and Psyllium Husk on Colonic Gene Expression and Histopathology, Mesenteric Lymph Node Immune Cells, and Disease Activity Index of Colitis Mice. (29th May 2020) - Lin, Ching-Yen; Lee, Anne; Chiu, Karen; Steelman, Andrew; Swanson, Kelly
Abstract: Objectives: The beneficial effects of supplementing yeast products in terms of promoting gut health have been demonstrated in several animal species. These benefits include promoting gut integrity, modulating gut microbiota, and positively affecting immune responses. With these benefits, yeast products may be a strategy to relieve clinical signs associated with colitis. The objective of this study was to investigate the effects of a yeast product (YP) on colonic gene expression and histopathology, mesenteric lymph node (MLN) immune cells, and disease activity index (DAI) in a dextran sulfate sodium (DSS)-induced colitis model. Psyllium husk (PH), which has been shown to be protective in this model, also was included. Methods: Fifty-four 6-week-old male C57BL/6J mice were assigned to: 1) AIN93G diet (control); 2) control diet + 5% YP; or 3) control diet + 5% PH. After 2 wk (d1–14) of diet adaptation, mice were provided with water or water + 3% (wt: vol) DSS for 5 d (d15–19). Body weight, food intake, water intake, and DAI data were recorded daily during the water/DSS treatment period. Mice were euthanized on d 20, followed by tissue collection. Data were analyzed using the Mixed Models procedure of SAS 9.4. Results: MLN immune cell populations and colonic histopathology were not affected ( P > 0.05) by diet. PH mice had greater ( P < 0.05) gene expression of Cldn2, Cldn3, Cldn8, and Ocln compared to control mice. DAI, immune cell numbers, colonic histopathology, and colonic gene expression were not affected ( P > 0.05) by YP in DSS mice. DSS mice consuming PH had lower ( P < 0.05) DAI compared to control or YP mice. Conclusions: Results suggest that YP at the dose tested failed to attenuate clinical signs or inflammation associated with colitis. PH, on the other hand, showed protective effects on DSS-induced colitis as reported previously. Funding Sources: This research was funded internally.